Reply: Enhancing diagnostic approaches for placental dysfunction in fetal growth restriction - Rodriguez-Sibaja, Maria J.; Lopez-Diaz, Jimena; Lumbreras-Márquez, Mario Isaac (Elsevier BV, 2025)
We appreciate Dr Carbillon's insightful commentary on our study comparing the performance of the International Society of Ultrasound in Obstetrics and Gynecology and the Society for Maternal-Fetal Medicine definitions of fetal growth restriction (FGR) in identifying maternal vascular malperfusion (MVM) lesions and adverse neonatal outcomes.1 His insights into the role of Doppler studies and angiogenic biomarkers in placental dysfunction diagnostics highlight important considerations for advancing FGR assessment. However, our study focused on the histopathological confirmation of MVM lesions associated with the FGR definitions mentioned above. We agree with Dr Carbillon that integrating uterine artery Doppler and angiogenic biomarkers, such as placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1–to–PlGF ratio, into the diagnostic framework for FGR could enhance the diagnostic precision of FGR and placental dysfunction, as supported by recent research and international guidelines. ©The authors ©American Journal of Obstetrics & Gynecology MFM ©Elsevier.
Keywords: Letter to the Editor